Structural elucidation of the exopolysaccharide produced by Curvularia lunata isolate RJ01 - JAY JAYUS; ROBBY AKROMAN; NURHAYATI NURHAYATI; ARI SATIA NUGRAHA; BAMBANG PILUHARTO; ROBERT JAMES SEVIOUR (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Jayus J, Akroman R, Nurhayati, Nugraha AS, Piluharto B, Seviour RJ. 2021. Structural elucidation of the exopolysaccharide produced by Curvularia lunata isolate RJ01. Biodiversitas 22: 2699-2705. An exopolysaccharide (EPS) was recovered from culture filtrates of the fungus Curvularia lunata isolate RJ01 prepared in Jember, Indonesia. Based on a prominent peak at 883 cm-1, FTIR analysis suggested it is a ?-D-glucan, a proposal confirmed by subsequent nuclear magnetic resonance (NMR) analysis which showed anomeric protons omit the signal at d4.37 and 4.8 ppm, and sugar proton signal in the region of 2.5 to 4.2 ppm. High-performance liquid chromatography (HPLC) analysis of the acid hydrolysates of this glucan revealed the presence of glucose (64%) and a mixture of galactose and mannose (36%). Digestion with (1-->3)-?- and (1-->6)-?-glucanase from Acremonium sp. IMI 383068 gave consistent linear products of (1-->3)-?-glycosidic linkages, since the glucan was digested by (1-->3)-?-glucanase only. The rheological behavior of aqueous EPS solution suggests it behaves as a pseudoplastic non-Newtonian fluid and thus has the potential for use as a thickening agent in foods. This study is the first report on the structural elucidation of EPS from C. lunata.